Yegorova O. I. Тypological aspects of the phraseo–semantic field of indefinite quantity - Yegorova O. I. (Philological Treatises, 2020)
The article in question deals with the phraseo–semantic field of indefinite quantity; the principles of the phraseological formations semantic classification on the material of distant languages are being identified. The attention is being focused on the typological parallels of phraseological units, lexico–grammatic deviation of their presentation.